Intralesional TTI-621, a novel biologic targeting the innate immune checkpoint CD47, in patients with relapsed or refractory mycosis fungoides or Sézary syndrome: a multicentre, phase 1 study. Issue 11 (November 2021) - Querfeld, Christiane; Thompson, John A; Taylor, Matthew H; DeSimone, Jennifer A; Zain, Jasmine M; Shustov, Andrei R; Johns, Carolyn; McCann, Sue; Lin, Gloria H Y; Petrova, Penka S; Uger, Robert A; Molloy, Naomi; et al.
Summary: Background: Intravenous TTI-621 (SIRPα-IgG1 Fc) was previously shown to have activity in relapsed or refractory haematological malignancies. This phase 1 study evaluated the safety and activity of TTI-621 in patients with percutaneously accessible relapsed or refractory mycosis fungoides, Sézary syndrome, or solid tumours. Here we report the clinical and translational results among patients with mycosis fungoides or Sézary syndrome. Methods: This multicentre, open-label, phase 1 study was conducted at five academic health-care and research centres in the USA. Eligible patients were aged 18 years or older; had injectable, histologically or cytologically confirmed relapsed or refractory cutaneous T-cell lymphoma (CTCL) or solid tumours; Eastern Cooperative Oncology Group performance status of 2 or less; and adequate haematological, renal, hepatic, and cardiac function. TTI-621 was injected intralesionally in a sequential dose escalation (cohorts 1–5; single 1 mg, 3 mg, or 10 mg injection or three 10 mg injections weekly for 1 or 2 weeks) and in expansion cohorts (cohorts 6–9; 2 week induction at the maximum tolerated dose; weekly continuation was allowed). In cohort 6, patients were injected with TTI-621 in a single lesion and in cohort 7, they were injected in multiple lesions. In cohort 8, TTI-621 was combined with pembrolizumab 200 mg injections per product labels. In cohort 9, TTI-621 was combined with the standard labelled dose of subcutaneous pegylated interferon alpha-2a 90 μg. The primary endpoint was the incidence and severity of adverse events. The study is registered with ClinicalTrials.gov, NCT02890368, and was closed by the sponsor to focus on intravenous studies with TTI-621. Findings: Between Jan 30, 2017, and March 31, 2020, 66 patients with mycosis fungoides, Sézary syndrome, other CTCL, or solid tumours were screened, 35 of whom with mycosis fungoides or Sézary syndrome were enrolled and received intralesional TTI-621 (escalation, n=13; expansion, n=22). No dose-limiting toxicities occurred; the maximum tolerated dose was not established. In the dose expansion cohorts, the maximally assessed regimen (10 mg thrice weekly for 2 weeks) was used. 25 (71%) patients had treatment-related adverse events; the most common (occurring in ≥10% of patients) were chills (in ten [29%] patients), injection site pain (nine [26%]), and fatigue (eight [23%]). No treatment-related adverse events were grade 3 or more or serious. There were no treatment-related deaths. Rapid responses (median 45 days, IQR 17–66) occurred independently of disease stage or injection frequency. 26 (90%) of 29 evaluable patients had decreased Composite Assessment of Index Lesion Severity (CAILS) scores; ten (34%) had a decrease in CAILS score of 50% or more (CAILS response). CAILS score reductions occurred in adjacent non-injected lesions in eight (80%) of ten patients with paired assessments and in distal non-injected lesions in one additional patient. Interpretation: Intralesional TTI-621 was well tolerated and had activity in adjacent or distal non-injected lesions in patients with relapsed or refractory mycosis fungoides or Sézary syndrome, suggesting it has systemic and locoregional abscopal effects and potential as an immunotherapy for these conditions. Funding: Trillium Therapeutics.